Pengaruh Ekspor dan Impor Terhadap Pertumbuhan Ekonomi di Indonesia Pada Tahun 2004- 2024 - Aditia Apriana; Heni Noviarita; Suhendar Suhendar (Journal of Business and Economics Research (JBE), 2026)
Economic growth is an important indicator in evaluating a country's development performance, which is influenced by international trade activities such as exports and imports. However, the relationship between exports, imports, and economic growth in Indonesia has shown inconsistent results in previous studies. This study aims to analyze the effect of exports and imports on economic growth in Indonesia during the period 2004–2024. This research applies a quantitative approach using secondary data in the form of time series obtained from the Central Bureau of Statistics (BPS). The analytical method employed is multiple linear regression supported by classical assumption tests, t-test (partial), F-test (simultaneous), and coefficient of determination analysis. The novelty of this study lies in the use of a longer and more updated observation period up to 2024 and the integration of economic analysis with an Islamic economic perspective in examining international trade activities. The results indicate that partially, exports and imports have a positive but not significant effect on economic growth. However, simultaneously exports and imports have a significant effect on economic growth with a probability value of 0.000212. The coefficient of determination shows that 60.93% of economic growth variation can be explained by export and import variables. This study contributes to enriching empirical studies on the role of international trade in economic growth and provides insights for policymakers in formulating sustainable trade policies.